EXPERIÊNCIAS DE JUVENTUDES DOS ESTUDANTES DE GEOGRAFIA DA FCT/UNESP E DO CPTL-UFMS - JOAO PEDRO TURINO SILVA (2023)
The central objective of this research is to apprehend and analyze the experiences of youth(s) that are present in the Geography course at the Faculdade de Ciências e Tecnologia, at the Universidade Estadual Paulista "Júlio de Mesquita Filho" (FCT/UNESP), Presidente Prudente, and in the Geography course at the Universidade Federal do Mato Grosso do Sul (CPTL-UFMS) Campus of Três Lagoas. As a general objective we sought to answer the following question: Who are the young people who arrive at the Geography course at UFMS and FCT/Unesp and what were their previous experiences of youth and what experiences do they have when they enter the course? To answer this question, we followed an investigative path that articulates quantitative and qualitative strategies of information production. We carried out 5 interviews (online), 2 focus groups, applied questionnaires, and accessed data from the undergraduate section of the FCT/UNESP. We hope that this research has brought a contribution to the Geography courses at FCT/UNESP and CPTL-UFMS, which will be able to get to know their respective students and thus perhaps rethink pedagogical strategies and actions to expand dialogue with undergraduates and with the community itself. We consider that the encounter of different trajectories in the university space in direct contact with the contents of geography modifies these young people, their education and worldviews, developing criticism and autonomy, beyond professional training. Key-words: Youths; Experience; Public University; Geography; CPTL-UFMS Três Lagoas; FCT/UNESP Presidente Prudente.